Importance of Security Culture in Control as a Function of Management in the Police - Radivojević, Nenad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Abstract: Control as a function of management in the police is accompanied by numerous problems, which are mainly related to the management process itself. One of these problems is the specific subculture in the police. Subculture in the police occurs, among other, as a result of tightness of the police, within which specific values, attitudes and behaviors are developed. This is particularly evident in the relation manager-subordinate. In fact, in practice it often happens that managers and subordinates unsympathetically look at each other. On the other hand, great solidarity between managers and subordinates can lead to a failure to implement control or situations of forging reports on the results of control, and so make it pointless in practice.This paper analyzes the security culture as a factor in the management of the police. Its importance in the context of control as a function of management is great because these managers, to a large extent, create the (security) culture in the police. Managers must be aware of the importance of control, in such a way that the control should not be neglected, but they also should not overdo it. In this regard, the paper points out the need for ongoing development and implementation of the concept of security culture in the police, with practical guidelines for working managers who will respect the basic principles and rules of security culture to achieve control objectives.Key words: police, security culture, functions of management, control problems.